Multicenter Analysis of Presacral Neuroendocrine Neoplasms—Clinicopathological Characterization and Treatment Outcomes of a Rare Disease - Matrood, Sami; Apostolidis, Leonidas; Schrader, Jörg; Krug, Sebastian; Lahner, Harald; Ramaswamy, Annette; Librizzi, Damiano; Kender, Zoltan; Kröcher, Anke; Kreutzfeldt, Simon; Gress, Thomas Matthias; Rinke, Anja (Frontiers in Endocrinology, 2021)
Background and aims: Neuroendocrine neoplasms (NEN) of the presacral space are an extremely rare disease entity with largely unknown outcome and no established standard of care treatment. Therefore, we wanted to analyze clinical presentation, histopathological findings, treatment outcomes and prognosis in a multicentric patient cohort. Methods: We searched local databases of 6 German NEN centres for patients with presacral NEN. Retrospective descriptive analyses of age, sex, stage at diagnosis, symptoms, grade, immunohistochemical investigations, biomarkers, treatment and treatment outcome were performed. Kaplan Meier Analysis was used to determine median overall survival. Results: We identified 17 patients (11 females, 6 males) with a median age of 50 years (range 35-66) at diagnosis. 12 cases presented initially with distant metastases including bone metastases in 9 cases. On pathologic review the majority of patients had well-differentiated G2 tumors. Immunohistochemical profile resembled rectal NENs. All but one patient had non-functioning tumors. Somatostatin receptor imaging was positive in 14 of 15 investigated cases. 8 patients were treated surgically including palliative resections, 14 patients received somatostatin analogs with limited efficacy. With 14 PRRTs completed, 79% showed clinical benefit, whereas only one patient with NEC responded to chemotherapy. Treatment with everolimus in 3 patients was not successful, whereas cabozantinib resulted in a disease stabilization in a heavily pretreated patient. During a median observation period of 44.5 months 6 patients died. Median overall survival was not reached. Conclusion: Presacral NEN are histopathologically similar to rectal NENs. Presacral NEN should be considered as possible primary in NEN of unknown primary. The majority of tumors is non-functioning and somatostatin receptor positive. PRRT demonstrated promising activity, tyrosine kinase inhibitors warrant further investigations. Further molecular characterization and prospective evaluation of this rare tumor entity is needed.